Pemanfaatan Media Sosial (Group Whatsapp) dalam Menunjang Aktifitas Belajar Siswa di Luar Jam Sekolah di SMK Negeri 2 Tulungagung - Reno Auliya Anggraini; Andreas Andrie Djatmiko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
In the current era of globalization, science and technology are developing rapidly, as is the case in Indonesia. Without realizing communication media has greatly influenced aspects of human life, the most popular use among students is social media as one of the communication tools between friends and with teachers and other people. The use of social media is mostly used by students and teachers using whatsapp social media to convey information quickly, for example information about school assignments, test schedules, or other information. The method used in this study is descriptive qualitative. The pengumoulan technique for the data includes; observation, interview and documentation. With the observation method on the researcher to obtain data about the actual condition of the conditions that exist between the homeroom teacher and students at State Vocational High School 2 Tulungagung. The documentation method itself is looking for data and circumstances related to the object of research and data related to this study. This interview method is used to obtain information directly from the resource person to find out the problems raised in this study. From the results of research using the method of observation, documentation and interviews. Thus the results of this study can be concluded that with the use of social media (whatsapp group) in supporting student learning activities outside school hours can provide changes to student learning activities in the classroom and also improve the value of student learning outcomes.